PENGARUH PROFITABILITAS, LEVERAGE, ENTERPRISE SIZE, DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021) - Hasna Isnabella; Rina Trisnawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Economic development in Indonesia is currently growing very fast, especially in the Indonesian economy, namely the consumer goods industry sector. The consumer goods industry is one of the most interesting industrial sectors, because all of its products are always needed by the community, even now Indonesia is a very large country with a large population. The consumer goods industry produces a product that is consumptive in nature and is liked by the whole community, such as food, medicine and others. This study aims to determine how the influence of profitability, leverage, enterprise size, and the audit committee on corporate social responsibility by using a quantitative approach and purposive sampling. The results of this study indicate that leverage has an effect on corporate social responsibility, while profitability, enterprise size, and audit committee have no effect on corporate social responsibility.